High glucose levels boost the aggressiveness of highly metastatic cholangiocarcinoma cells via O-GlcNAcylation - Phoomak, Chatchai (Sci Rep, 2017)
Increased glucose utilization is a feature of cancer cells to support cell survival, proliferation, and metastasis. An association between diabetes mellitus and cancer progression was previously demonstrated in cancers including cholangiocarcinoma (CCA). This study was aimed to determine the effects of high glucose on protein O-GlcNAcylation and metastatic potentials of CCA cells. Two pairs each of the parental low metastatic and highly metastatic CCA sublines were cultured in normal (5.6 mM) or high (25 mM) glucose media. The migration and invasion abilities were determined and underlying mechanisms were explored. Results revealed that high glucose promoted migration and invasion of CCA cells that were more pronounced in the highly metastatic sublines. Concomitantly, high glucose increased global O-GlcNAcylated proteins, the expressions of vimentin, hexokinase, glucosamine-fructose-6-phosphate amidotransferase (GFAT) and O-GlcNAc transferase of CCA cells. The glucose level that promoted migration/invasion was shown to be potentiated by the induction of GFAT, O-GlcNAcylation and an increase of O-GlcNAcylated vimentin and vimentin expression. Treatment with a GFAT inhibitor reduced global O-GlcNAcylated proteins, vimentin expression, and alleviated cell migration. Altogether, these results suggested the role of high glucose enhanced CCA metastasis via modulation of O-GlcNAcylation, through the expressions of GFAT and vimentin.